Discrepancy Between Neuroimaging Findings and Clinical Phenotype in Alexander Disease - Dinopoulos, A.; Gorospe, J.R.; Egelhoff, J.C.; Cecil, K.M.; Nicolaidou, P.; Morehart, P.; DeGrauw, T. (American Journal of Neuroradiology, 2006)
SUMMARY: We present a case of infantile-onset Alexander disease (AD) with a novel glial fibrillary acidic protein mutation but without clinical evidence of neurologic deterioration. Brain MRI studies showed typical AD findings and increasing size of frontal cavitations. Serial proton MR spectroscopy demonstrated high levels of myo-inositol and lactic acid and decreasing levels of N-acetylaspartate. The degree of demyelination and the timing of the axonal degeneration may determine phenotypic severity of the disease. Conventional neuroimaging techniques cannot always predict the outcome.